Vítimas, autores e testemunhas de bullying : uma avaliação das habilidades sociais e de indicadores da competência social - Comodo, Camila Negreiros (2016)
The literature has shown evidence that bullying is a worldwide phenomenon that deserves the attention of researchers and the community as a whole. Considering that bullying occurs in interpersonal relationships among students, it is important to understand the role of social skills repertoire of these individuals and their social competence to deal with the bullying situation, as a way to provide a more accurate diagnosis on the relationship of social skills and bullying, as well as contribute for the prevention of this type of violence. Considering these aspects, this study aimed to: (1) correlate social skills classes with authoring and victimization bullying behaviors; (2) compare the social skills of victims, authors, victims-authors and bystanders of bullying in terms of frequency and difficulty; (3) identify similarities and differences between the scores of authorship and victimization in bullying considering the self-assessment, peers and teachers evaluations; (4) assess and describe social competence indicators of teenagers involved in bullying; (5) functionally analyze the behavior of victims, perpetrators and bystanders of bullying. To analyze the social skills of students involved in bullying were applied the IHSA-Del-Prette, QIPVE and Peer Assessment with 241 adolescents aged 11 to 16 years. The data were analyzed descriptively and inferentially, and it was found that bullying behaviors and victimization showed a negative correlation with social skills classes. It was also found that students involved in bullying reported a less elaborate repertoire of self-control, assertiveness and empathy. Additionally, a comparison was also made between the bullying instruments used in this study. For this purpose 263 students responded to QIPVE and Peer Assessment, and 10 teachers appointed students as victims and bullies. This comparison brought data that there are differences between the self-assessment, evaluation of teachers and peers nominations about the involvement in bullying. To assess social competence indicators was realized an interview with 10 bullies, eight victims, 10 victims-authors and 10 bystanders. The interviews were transcribed and the responses were categorized. The results indicated that all respondents reported fail to achieve important indicators of social competence, which brings an impact on quality of life and development of these adolescents. Finally, the functional analysis of the student´s behavior pointed out that the attacks made by the bullies are reinforced by the removal of the victims and the bystanders’ silence and/or laughter. These datas indicate that anti-bullying programs should teach some specific social skills classes, promote not only social skills but also social competence and reach the entire school community, including bystander.